2008
DOI: 10.1161/circulationaha.107.731877
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Interleukin-1 by Anakinra Improves Vascular and Left Ventricular Function in Patients With Rheumatoid Arthritis

Abstract: Background-Interleukin-1 increases nitrooxidative stress. We investigated the effects of a human recombinant interleukin-1a receptor antagonist (anakinra) on nitrooxidative stress and vascular and left ventricular function. Methods and Results-In an acute, double-blind trial, 23 patients with rheumatoid arthritis were randomized to receive a single injection of anakinra (150 mg SC) or placebo and, after 48 hours, the alternative treatment. At baseline and 3 hours after the injection, we assessed (1) coronary f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
195
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 273 publications
(213 citation statements)
references
References 39 publications
8
195
0
6
Order By: Relevance
“…26 Owing to the small number of patients or perhaps because of a different inciting event, we did not observe a significant reduction in C-reactive protein. Nevertheless, a significant correlation was seen between the C-reactive protein changes and LV remodeling.…”
Section: Discussionmentioning
confidence: 63%
“…26 Owing to the small number of patients or perhaps because of a different inciting event, we did not observe a significant reduction in C-reactive protein. Nevertheless, a significant correlation was seen between the C-reactive protein changes and LV remodeling.…”
Section: Discussionmentioning
confidence: 63%
“…Also in synovial fluids obtained from RA patients the levels of RONS including superoxide are significantly raised and positively correlated with higher Nox activity (62). In addition, increased levels of nitrotyrosine, another marker of oxidative stress, were detected in RA patients (63) and also in TTP Ϫ/Ϫ mice (Fig. 4D).…”
Section: Discussionmentioning
confidence: 80%
“…It decreases necrosis of cardiac tissue following acute myocardial infarctions 2 , and thereby attenuates cardiac remodeling and prevents apoptosis and subsequent postinfarct complications such as cardiac failure. In patients with RA, anakinra increases the coronary flow reserve and decreases endothelin-1 levels, improving left ventricular function in these patients 3 . Similarly, Chada, et al have shown in an animal model that when anakinra is administered as an aerosol to surfactantdepleted lungs it reduces pulmonary inflammation, but also has a negative effect on the pulmonary artery pressure and thus ameliorates associated pulmonary hypertension 4 .…”
Section: To the Editormentioning
confidence: 99%